Lithium secondary battery

By using a non-aqueous electrolyte containing specific cations and oxalate complex anions in a lithium secondary battery, dendrites of lithium metal are inhibited and a stable coating is formed, and the problem of degradation of the circulation characteristics of lithium secondary batteries is solved. Achieve higher discharge capacity maintenance and battery stability.

CN114375518BActive Publication Date: 2025-01-14PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080059949.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-07-28
Publication Date
2025-01-14
Estimated Expiration
2040-07-28

AI Technical Summary

Technical Problem

When lithium secondary batteries are charged, lithium metal is prone to form dendrites, resulting in an increase in the surface area of ​​the negative electrode, an increase in side reactions, and a decrease in discharge capacity and circulation characteristics. The existing technology has insufficient effect on suppressing the precipitation of dendrites, and there is a limit to improving circulation characteristics.

Method used

Non-aqueous electrolytes containing cationic ions, Na, K, Rb, Cs, Fr, Mg, Ca, Sr, Ba and Al and oxalate complex anions are used to precipitate the cation and lithium ions and grass. The stabilization effect of the anions of the acid salt complex inhibits the precipitation of dendrites of lithium metal, forms a stable coating, and improves the circulation characteristics of lithium secondary batteries.

Benefits of technology

It significantly improves the circulation characteristics of lithium secondary batteries, improves the maintenance rate of discharge capacity, extends the service life of the battery, and enhances the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114375518B_ABST
    Figure CN114375518B_ABST
Patent Text Reader

Abstract

A lithium secondary battery comprises: a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein lithium metal is precipitated in the negative electrode during charging and dissolved in the non-aqueous electrolyte during discharging, and the non-aqueous electrolyte comprises cations and anions, the cations comprising lithium ions and comprising at least one cation X selected from the group consisting of Na, K, Rb, Cs, Fr, Mg, Ca, Sr, Ba and Al, and the anions comprising oxalate complex anions Y.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a lithium secondary battery using lithium metal as a negative electrode active material. Background Art

[0002] Non-aqueous electrolyte secondary batteries are used, for example, in ICT applications such as computers and smart phones, in-vehicle applications, and in applications such as power storage applications. In such applications, further high capacity is required for non-aqueous electrolyte secondary batteries. As a high-capacity non-aqueous electrolyte secondary battery, a lithium ion battery is known. The high capacity of a lithium ion battery can be achieved by combining alloy active materials such as graphite and silicon compounds as negative electrode active materials. However, the high capacity of lithium ion batteries has gradually reached its limit.

[0003] As a non-aqueous electrolyte secondary battery with a higher capacity than lithium-ion batteries, lithium secondary batteries are promising. In lithium secondary batteries, lithium metal is precipitated in the negative electrode during charging, and the lithium metal is dissolved in the non-aqueous electrolyte during discharge. It should be noted that lithium secondary batteries are sometimes called lithium metal secondary batteries.

[0004] In lithium batteries, lithium metal is precipitated in the negative electrode during charging. At this time, lithium metal may be precipitated in the form of dendrites. However, if dendrites are generated, the specific surface area of ​​the negative electrode tends to increase and side reactions tend to increase. Therefore, the discharge capacity and cycle characteristics tend to decrease.

[0005] Non-Patent Document 1 describes that the precipitation of dendrites can be suppressed by adding cesium ions or rubidium ions to an electrolyte.

[0006] Prior art literature

[0007] Non-patent literature

[0008] Non-patent document 1: Fei Ding, et al., “Dendrite-Free Lithium Deposition via Self-Healing Electrostatic Shield Mechanism”, J. Am. Chem. Soc., 2013, 135, p. 4450-4456 Summary of the invention

[0009] However, in Non-Patent Document 1, the effect of suppressing the precipitation of dendrites is not sufficient, and there is a limit to the improvement of the cycle characteristics of the lithium secondary battery.

[0010] One aspect of the present disclosure relates to a lithium secondary battery comprising: a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein lithium metal is precipitated in the negative electrode during charge and the lithium metal is dissolved in the non-aqueous electrolyte during discharge, the non-aqueous electrolyte comprises cations and anions, the cations comprise lithium ions and comprise at least one cation X selected from the group consisting of Na, K, Rb, Cs, Fr, Mg, Ca, Sr, Ba and Al, and the anions comprise oxalate complex anions Y.

[0011] In lithium secondary batteries, cycle characteristics are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 1 is a longitudinal cross-sectional view schematically showing a lithium secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0013] A lithium secondary battery according to an embodiment of the present disclosure comprises: a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode. In the negative electrode, lithium metal is precipitated during charging, and the lithium metal is dissolved in the non-aqueous electrolyte during discharge. The non-aqueous electrolyte comprises cations and anions. The cations comprise lithium ions and comprise at least one cation X selected from the group consisting of Na, K, Rb, Cs, Fr, Mg, Ca, Sr, Ba, and Al. The anions comprise an oxalate complex anion Y. The cation X is generally composed of Na + , K + , Rb + , Cs + , Fr + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ 、Al 3+ Etc. indicates.

[0014] In lithium secondary batteries, the precipitation and dissolution of lithium metal are repeated in the negative electrode by charging and discharging. In lithium secondary batteries, lithium metal is almost always present in the negative electrode. Therefore, in lithium secondary batteries, the contact opportunities between lithium metal and non-aqueous electrolyte are increased compared with lithium ion batteries, and the side reactions between the two tend to become significant.

[0015] In addition, for lithium secondary batteries, lithium metal is easily precipitated in a dendrite shape compared to lithium ion batteries. If lithium metal is precipitated in a dendrite shape, the specific surface area of ​​lithium metal increases. As a result, the side reaction of lithium metal and electrolyte further increases. As a result, the reduction of discharge capacity becomes significant, and the cycle characteristics are easily greatly reduced.

[0016] In the lithium secondary battery of this embodiment, during charging, the cation X contained in the electrolyte preferentially coprecipitates with the lithium ions, and an alloy containing lithium and the cation X is precipitated in the negative electrode. It is believed that such coprecipitation will proceed more stably than when only the lithium ions receive electrons and precipitate.

[0017] In addition, it is believed that the oxalate complex anion Y contained in the electrolyte has the effect of stabilizing the lithium ions and the cations X, and plays a role in suppressing the local co-precipitation of the lithium ions and the cations X. As a result, it is believed that the precipitation of dendrites can be suppressed, and the cycle characteristics are significantly improved. It is believed that the fact that the oxalate complex anion Y is easily coordinated in a manner of encapsulating the cations affects the stabilization of the cations.

[0018] Furthermore, if the oxalate complex anion Y is decomposed in the negative electrode, a stable coating is formed on the surface of the negative electrode. It is believed that the oxalate complex anion Y is preferentially decomposed over other components contained in the electrolyte, and a uniform and soft coating is formed on the surface of the negative electrode. In addition, it is believed that by introducing lithium ions and cations X having different ionic radii into such a coating, the precipitation starting point of lithium metal becomes uniform, and the co-precipitation of lithium ions and cations X becomes further facilitated. As a result, the precipitation of dendrites is further suppressed.

[0019] The oxalate complex anion Y can be selected from B(C 2 O 4 ) 2 - , BF 2 (C 2 O 4 ) - , P(C 2 O 4 ) 3 - PF 2 (C 2 O 4 ) 2 - and PF 4 (C 2 O 4 ) - At least one of the group consisting of. It is believed that these have a great effect of stably co-precipitating lithium ions and cations X. It is believed that the oxalate complex anion Y containing fluorine has a great effect.

[0020] The cation X and the oxalate complex anion Y may be contained in the nonaqueous electrolyte in the form of their salts, or a salt of the cation X and other anions and a lithium salt of the oxalate complex anion Y may be contained in the nonaqueous electrolyte.

[0021] The structure of the lithium secondary battery will be described in more detail below.

[0022] [negative electrode]

[0023] The negative electrode usually has a negative electrode collector. For example, a metal foil can be used as the negative electrode collector. The negative electrode has a layer containing lithium metal (lithium metal layer or lithium alloy layer) at least when charged. The open circuit potential of the negative electrode when fully charged is, for example, 0V or more and 70mV or less relative to lithium metal.

[0024] Full charge means: when the rated capacity of the battery is set to C, for example, the battery is charged to a state of charge (SOC: State of Charge) of 0.98×C or more. The open circuit potential of the negative electrode when fully charged can be measured by disassembling the fully charged battery in an argon atmosphere, removing the negative electrode, and assembling a battery cell with lithium metal as the counter electrode. The non-aqueous electrolyte of the battery cell can be the same composition as the non-aqueous electrolyte in the disassembled battery, for example, the electrolyte used in Example 1 described later can be used as a model electrolyte.

[0025] As the metal constituting the negative electrode collector, a metal that does not react with lithium metal is preferred, for example, copper (Cu), nickel (Ni), iron (Fe) and alloys containing these metal elements can be listed. As alloys, copper alloys, stainless steel (SUS) and the like are preferred. Among them, copper and / or copper alloys are preferred from the perspective of excellent conductivity. The copper content in the negative electrode collector is preferably 50% by mass or more, and can also be 80% by mass or more. The thickness of the negative electrode collector is not particularly limited, for example, 5 μm to 20 μm.

[0026] The negative electrode may include a negative electrode collector and a plurality of layers stacked on the negative electrode collector. The plurality of layers may include, for example, a first layer and a second layer. The first layer includes a material capable of absorbing lithium ions, and the second layer includes lithium metal. In this case, the first layer is arranged closer to the negative electrode collector than the second layer. The first layer helps the negative electrode collector and allows lithium ions to be uniformly deposited on the negative electrode collector in the initial stage of charging.

[0027] As the material capable of absorbing lithium ions contained in the first layer, for example, a material that can be used as a negative electrode active material of a lithium ion battery can be used. Specifically, a carbon material capable of electrochemically absorbing and releasing lithium ions, a metal that can alloy with lithium, a metal compound, etc. can be used. In addition, a film of a metal that can alloy with lithium can also be formed as the first layer. Specific examples of metals forming the metal film include aluminum, zinc, silicon, tin, etc.

[0028] [positive electrode]

[0029] The positive electrode includes: a positive electrode mixture layer containing a positive electrode active material, and a positive electrode collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry containing a positive electrode active material, a binder, a conductive agent, etc. dispersed in a dispersion medium to the surface of the positive electrode collector and drying it. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode collector or on both surfaces.

[0030] When the positive electrode active material includes a composite oxide containing lithium and a transition metal, the total amount of lithium in the positive electrode and the negative electrode is M Li The amount of transition metal in the positive electrode M TM Molar ratio: M Li / M TM That is, in a lithium secondary battery (lithium metal secondary battery), lithium involved in charge and discharge is substantially (or entirely) derived from a composite oxide containing lithium and a transition metal as a positive electrode active material.

[0031] Here, the total amount of lithium in the positive electrode and the negative electrode is M Li It refers to the total amount of lithium contained in the positive electrode mixture layer per unit area and the negative electrode (more specifically, the total of the first layer and the second layer) per unit area opposite thereto. TM It refers to the amount of transition metal contained in the positive electrode mixture layer per unit area.

[0032] The molar ratio of lithium to transition metal contained in the composite oxide: lithium / transition metal may be, for example, 0.9 to 1.1.

[0033] Examples of such positive electrode active materials include layered rock salt type composite oxides. Specifically, examples of positive electrode active materials include Li a CoO 2 , Li a NiO 2 , Li a MnO 2 , Li a Co b Ni 1-b O 2 , Li a Co b M 1-b O c (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Ni, Cu, Zn, Al, Cr, Pb, Sb and B), Li a Ni b M 1-b O c(M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Cu, Zn, Al, Cr, Pb, Sb, and B), LiMPO 4 (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, 0 < a ≤ 1.1, 0 ≤ b ≤ 0.9, and 2 ≤ c ≤ 2.3. It should be noted that the value of a representing the molar ratio of lithium increases or decreases due to charge and discharge.

[0034] Among them, a layered rock salt-type composite oxide containing nickel element is preferably used. Such a composite oxide is composed of Li a Ni x M 1-x O 2 (M is at least one selected from the group consisting of Mn, Co, and Al, satisfying 0 < a ≤ 1.1, 0.3 ≤ x ≤ 1). From the viewpoint of high capacity, it is preferably 0.85 ≤ x ≤ 1. Furthermore, from the viewpoint of the stability of the crystal structure, a lithium-nickel-cobalt-aluminum composite oxide (NCA) containing Co and Al as M is further preferred: Li a Ni x Co y Al z O 2 (0 < a ≤ 1.1, 0.85 ≤ x < 1, 0 < y < 0.15, 0 < z ≤ 0.1, x + y + z = 1). As a specific example of NCA, LiNi 0.8 Co 0.15 Al 0.05 O 2 , LiNi 0.8 Co 0.18 Al 0.02 O 2 , LiNi 0.9 Co 0.05 Al 0.05 O 2 etc.

[0035] As the binder, resin materials can be exemplified, such as fluororesins such as PTFE and PVdF; polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, poly(methyl acrylate), and ethylene-acrylic acid copolymer; vinyl resins such as PAN and poly(vinyl acetate); polyvinylpyrrolidone; polyethersulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These can be used alone or in combination of two or more.

[0036] As the conductive agent, for example, graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as phenylene derivatives, etc. These may be used alone or in combination of two or more.

[0037] The shape and thickness of the positive electrode current collector can be selected from the shape and range based on the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum (Al), aluminum alloy, and titanium.

[0038] [Non-aqueous electrolyte]

[0039] The non-aqueous electrolyte has lithium ion conductivity and contains cations and anions, wherein the cations contain lithium ions and cations X, and the anions contain oxalate complex anions Y.

[0040] The non-aqueous electrolyte may be an electrolyte solution (i.e., liquid) containing a solvent, and may be in a gel state or a solid state. The gel-like non-aqueous electrolyte comprises a liquid non-aqueous electrolyte (electrolyte) and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs the non-aqueous solvent and gels may be used. As such a polymer material, fluororesins, acrylic resins, and / or polyether resins may be cited.

[0041] Hereinafter, the electrolyte solution will be described in further exemplary detail.

[0042] The electrolyte solution can be prepared, for example, by dissolving a lithium salt and an oxalate complex salt in a solvent. The lithium salt can be used alone or in combination of two or more. The oxalate complex salt can be used alone or in combination of two or more. In this case, a portion of the lithium salt can be an oxalate complex salt, and at least a portion of the oxalate complex salt can also be a salt of cation X.

[0043] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO 4 、LiAlCl 4 , LiB 10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF 6 、LiPF 2 O 2 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiCF 3 SO 3 、LiCF 3 CO 2etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc.

[0044] As the lithium salt, a lithium salt of a fluorinated imide can be used. Such a salt contains a fluorinated imide anion. Examples of the fluorinated imide anion include a bis(fluorosulfonyl)imide anion (N(SO 2 F) 2 - ) (also known as FSI), bis(trifluoromethylsulfonyl)imide anion (N(SO 2 CF 3 ) 2 - ) (also known as FSIT), bis(perfluoroethylsulfonyl)imide anion (N(SO 2 C 2 F 5 ) 2 - )wait.

[0045] As solvent, for example, cyclic carbonate, chain carbonate, cyclic carboxylic acid ester, chain carboxylic acid ester etc. can be used. As cyclic carbonate, propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) etc. can be listed. As chain carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) etc. can be listed. In addition, as cyclic carboxylic acid ester, gamma-butyrolactone (GBL), gamma-valerolactone (GVL) etc. can be listed. As chain carboxylic acid ester, methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate (EP) etc. can be listed. Solvent can be used alone or in combination of two or more.

[0046] Examples of the solvent include cyclic ethers, chain ethers, nitriles such as acetonitrile, and amides such as dimethylformamide.

[0047] Examples of the cyclic ether include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, and crown ethers.

[0048] Examples of the chain ethers include 1,2-dimethoxyethane, dimethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0049] The contents of the lithium salt, the cation X, and the oxalate complex anion Y in the electrolyte solution can be measured by, for example, using NMR, ion chromatography, or the like.

[0050] The concentration of lithium ions in the electrolyte is, for example, 0.5 mol / liter or more and 3.5 mol / liter or less, 1 mol / liter or more and 2 mol / liter or less, or 1 mol / liter or more and 1.5 mol / liter or less. By setting the lithium ion concentration to the above range, an electrolyte having excellent ion conductivity and appropriate viscosity can be obtained. The oxalate complex anion Y can also be added to the electrolyte in the form of a lithium salt.

[0051] The concentration of the cation X in the electrolyte is, for example, 0.01 mol / liter or more and 0.5 mol / liter or less, and may be 0.05 mol / liter or more or 0.1 mol / liter or more. In this case, a sufficient improvement effect of the capacity retention rate can be obtained. In addition, sufficient lithium ion conductivity can be obtained.

[0052] The concentration of the oxalate complex anion Y in the electrolyte may be, for example, 0.5 mol / liter or less. In this case, the generation of gas due to the decomposition of the oxalate complex anion Y can be significantly suppressed, and an electrolyte having excellent ion conductivity and moderate viscosity can be easily obtained. From the viewpoint of more significant improvement in cycle characteristics, the concentration of the oxalate complex anion Y in the electrolyte may also be, for example, 0.01 mol / liter or more.

[0053] From the viewpoint of obtaining an electrolyte solution with better lithium ion conductivity, for example, an electrolyte solution containing LiPF 6 In the case of lithium salt, the content of the oxalate complex anion Y on a molar basis relative to the PF contained in the electrolyte can also be calculated. 6 - The ratio of the content of the ions on a molar basis is set to be 0.1 or more and 0.5 or less.

[0054] [Separator]

[0055] A separator is sandwiched between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, woven fabric, non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0056] [Lithium secondary battery]

[0057] Figure 1 This is a longitudinal cross-sectional view of an example of a cylindrical lithium secondary battery according to one embodiment of the present invention.

[0058] The lithium secondary battery 100 is a wound type battery including a wound electrode group 40 and a non-aqueous electrolyte (not shown). The wound electrode group 40 includes a strip-shaped positive electrode 10, a strip-shaped negative electrode 20, and a separator 30. A positive electrode lead 13 is connected to the positive electrode 10, and a negative electrode lead 23 is connected to the negative electrode 20.

[0059] One end of the positive lead 13 in the longitudinal direction is connected to the positive electrode 10, and the other end is connected to the sealing plate 90. The sealing plate 90 has a positive terminal 15. One end of the negative lead 23 is connected to the negative electrode 20, and the other end is connected to the bottom of the battery case 70 which becomes the negative terminal. The battery case 70 is a bottomed cylindrical battery can, one end of which is open in the longitudinal direction, and the bottom of the other end becomes the negative terminal. The battery case (battery can) 70 is made of metal, for example, formed of iron. The inner surface of the iron battery case 70 is usually nickel-plated. An upper insulating ring 80 and a lower insulating ring 60 made of resin are respectively arranged above and below the wound electrode group 40.

[0060] In the example, a cylindrical lithium secondary battery with a wound electrode group is described, but it is not limited to this case, and this embodiment can be applied. The shape of the lithium secondary battery can be appropriately selected from various shapes such as cylindrical, coin-shaped, square, sheet-shaped, flat, etc. according to its use. The form of the electrode group is not particularly limited, and it can also be a stacked type. In addition, for the composition other than the negative electrode of the lithium secondary battery, a known composition can be used without particular restriction.

[0061] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0062] [Example 1]

[0063] (1) Preparation of positive electrode

[0064] The lithium-containing composite oxide (LiNi 0.9 Co 0.05 Al 0.05 O 2), acetylene black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone (NMP) were mixed in a predetermined mass ratio to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an aluminum foil as a positive electrode current collector, and the coating was dried and then rolled to form a positive electrode mixture layer on both sides of the aluminum foil.

[0065] (2) Preparation of negative electrode

[0066] An electrolytic copper foil (thickness: 10 μm) was cut into a predetermined electrode size to obtain a negative electrode current collector.

[0067] (3) Preparation of electrolyte

[0068] LiPF as a lithium salt was added to a mixed solvent containing fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl ether (DME) in a volume ratio of 4:1:15. 6 , and cesium difluorooxalatoborate (CsBF 2 (C 2 O 4 )) (represented as CsFOB in Table 1.), and an electrolyte was prepared. LiPF in the electrolyte 6 The concentration of CsBF in the electrolyte is 1.0 mol / L. 2 (C 2 O 4 ) concentration is 0.1 mol / liter.

[0069] (4) Battery production

[0070] Lead tabs were installed on each electrode, and the positive electrode and the negative electrode were wound in a spiral shape with the separator sandwiched so that the lead was located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an outer casing made of a laminated film with aluminum foil as a barrier layer, and after vacuum drying at 105°C for 2 hours, an electrolyte was injected, and the opening of the outer casing was sealed to obtain a battery A1.

[0071] [Example 2]

[0072] In the preparation of electrolyte, instead of CsBF 2 (C 2 O 4 ) and magnesium difluorooxalate borate (Mg(BF 2 (C 2 O 4 )) 2 ) (Represented as MgFOB in Table 1 2 Mg(BF) in the electrolyte 2 (C 2 O 4 )) 2The concentration of MgO was 0.1 mol / L. Battery A2 was obtained in the same manner as in Example 1 except for the above.

[0073] [Comparative Example 1]

[0074] In the preparation of electrolyte, instead of CsBF 2 (C 2 O 4 ) and use CsPF 6 . CsPF in electrolyte 6 The concentration of MgO was 0.1 mol / L. Battery B1 was obtained in the same manner as in Example 1 except for the above.

[0075] [Comparative Example 2]

[0076] In the preparation of electrolyte, instead of CsBF 2 (C 2 O 4 ) and Mg(N(SO 2 CF 3 ) 2 ) 2 (In Table 1, it is represented as MgTFSI 2 ). (N(SO 2 CF 3 ) 2 ) 2 The concentration of MgO was 0.1 mol / L. Battery B2 was obtained in the same manner as in Example 1 except for the above.

[0077] [Comparative Example 3]

[0078] In the preparation of the electrolyte, CsBF was not used. 2 (C 2 O 4 ). Except for this, a battery B3 was obtained in the same manner as in Example 1.

[0079] [Evaluation 1]

[0080] The obtained batteries A1, A2, and B1 to B3 were subjected to charge and discharge tests.

[0081] In the charge and discharge test, the battery was charged in a thermostatic chamber at 25°C under the following conditions, then paused for 20 minutes and discharged under the following conditions. The charge and discharge were regarded as one cycle, and the charge and discharge test was performed for 50 cycles. The value obtained by dividing the discharge capacity of the 50th cycle by the discharge capacity of the first cycle was taken as the capacity retention rate (%). The evaluation results are shown in Table 1.

[0082] (Charging) Constant current charging was performed at a current of 0.3 It until the battery voltage reached 4.1 V, and then constant voltage charging was performed at a voltage of 4.1 V until the current value reached 0.02 It.

[0083] (Discharge) Constant current discharge was performed at a current of 0.3 It until the battery voltage reached 2.85V.

[0084] [Table 1]

[0085]

[0086] In Table 1, it can be seen that the capacity retention rate is significantly improved when the electrolyte contains both cation X and oxalate complex anion Y. On the other hand, the capacity retention rate of batteries B1 and B2 whose electrolyte contains only cation X is lower than that of battery B3 which does not contain cation X.

[0087] [Reference Example 1]

[0088] Graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and water as negative electrode active materials were mixed in a predetermined mass ratio to prepare negative electrode slurry. Next, the negative electrode slurry was applied to the surface of copper foil as a negative electrode current collector, and the coating was dried and then rolled to form a negative electrode mixture layer on both sides of the copper foil.

[0089] A battery R1 was obtained in the same manner as in Example 1 except that the above-mentioned negative electrode was used.

[0090] [Reference Example 2]

[0091] A battery R2 in which the electrolyte solution contained neither the cation X nor the oxalate complex anion Y was obtained in the same manner as in Comparative Example 3 except that the negative electrode of Reference Example 1 was used.

[0092] [Evaluation 2]

[0093] The obtained batteries R1 and R2 were subjected to a charge and discharge test in the same manner as in Evaluation 1. Table 2 shows the evaluation results.

[0094] [Table 2]

[0095]

[0096] In Table 2, no significant difference was observed between batteries R1 and R2 in terms of capacity retention. From this result, it can be understood that the synergistic effect brought about by the electrolyte containing both cation X and oxalate complex anion Y is a unique effect of lithium secondary batteries in which lithium metal is precipitated at the negative electrode during charging and dissolved in the electrolyte during discharging.

[0097] Industrial Applicability

[0098] The lithium secondary battery of the present invention has excellent cycle characteristics and can be used in electronic devices such as mobile phones, smartphones, and tablet terminals, electric vehicles including hybrid and plug-in hybrid vehicles, and household storage batteries combined with solar cells.

[0099] Description of Reference Numerals

[0100] 10 Positive electrode

[0101] 13 Positive lead

[0102] 15 Positive terminal

[0103] 20 Negative electrode

[0104] 23 Negative lead

[0105] 30 Dividers

[0106] 40 Wound Electrode Group

[0107] 60 Lower insulation ring

[0108] 70 Battery housing

[0109] 80 Upper insulation ring

[0110] 90 Sealing plate

[0111] 100 Lithium secondary battery

Claims

1. A lithium secondary battery comprising: a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode, The negative electrode is an electrode including a negative electrode current collector, wherein lithium metal is deposited during charging and the lithium metal is dissolved in the non-aqueous electrolyte during discharging. The nonaqueous electrolyte comprises cations and anions, The cations include lithium ions and include at least one cation X selected from the group consisting of Na, K, Rb, Cs, Fr, Mg, Ca, Sr, Ba and Al, The anion comprises an oxalate complex anion Y, The oxalate complex anion Y comprises fluorine, The concentration of the oxalate complex anion Y containing the fluorine in the non-aqueous electrolyte is 0.01 mol / liter or more and 0.5 mol / liter or less, The negative electrode does not contain a material capable of absorbing lithium ions.

2. The lithium secondary battery according to claim 1, wherein The oxalate complex anion Y is selected from BF2(C2O4) - PF2(C2O4)2 - , and PF4(C2O4) - At least one of the group consisting of.

3. The lithium secondary battery according to claim 1 or 2, wherein: The concentration of the cation X in the nonaqueous electrolyte is 0.01 mol / liter or more and 0.5 mol / liter or less.

4. The lithium secondary battery according to claim 1 or 2, wherein: The concentration of the lithium ions in the nonaqueous electrolyte is 0.5 mol / liter or more and 3.5 mol / liter or less.

5. The lithium secondary battery according to claim 1 or 2, wherein: The positive electrode comprises: a positive electrode mixture layer containing a positive electrode active material, and a positive electrode current collector. The positive electrode active material includes a composite oxide containing lithium and a transition metal. The total amount of lithium in the positive electrode and the negative electrode is M Li The amount M of the transition metal in the positive electrode TM Molar ratio: M Li / M TM Below 1.

1.

6. The lithium secondary battery according to claim 1 or 2, wherein: The non-aqueous electrolyte comprises PF6 - ion, The molar content of the oxalate complex anion Y in the electrolyte is relative to the PF6 - The ratio of the content of the ions on a molar basis is 0.1 or more and 0.5 or less.

Citation Information

Patent Citations

  • Non-aqueous electrolyte solution and non-aqueous electrolyte solution secondary battery using the same

    CN103762381A

  • Additives for galvanic cells

    CN105144459A

  • Non-aqueous electrolyte secondary battery

    CN109937504A